(untitled) (Third Sector Social Economic Review, 2023)
Although they vary from country to country, changes in the understanding of the state have brought about the active involvement of different actors such as the private sector and civil society in the execution of basic activities such as education and health. In this context, today’s rapid population growth, migration wave, educational inequalities, etc. It is seen that, in addition to the states, the private sector and non-governmental organizations are dynamically involved in the process and take responsibility on these issues. Volunteers who use their knowledge, skills and time for those in need stand out in assuming this responsibility. It is also mentioned that volunteering has a positive effect on social capital and social harmony. This is one of the indicators of how important volunteering is in contributing to social development. The main purpose of this research is to understand and explain the process experienced by people who carry out volunteering activities individually or in an organized manner, on the way to volunteering. In the qualitatively designed research, reports published within the scope of civil society, volunteering and philanthropy and interviews conducted within this scope were compiled as a data set. The most important findings that emerged in the study in which content analysis was made were family, values/overlap of values, religious belief, and childhood. Although values are a prominent finding in studies conducted in the field of volunteering, education, profession, and the conditions of the current period were also prominent findings in this study.